SIMULASI GAWAT DARURAT MENINGKATKAN SIKAP ORANG TUA DALAM PENANGANAN KEJANG DEMAM ANAK - Nurhadi, Mokhamad; Tiara Putri Ryandini; Hanim Nur Faizah; mokhamad; Moh Ubaidillah Faqih (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Febrile seizures are an emergency condition that can be life-threatening or life-threatening in children. Many parents do not understand the attitude in handling children’s febrile seizures so it can worsen the child’s condition if it is too late to get help. Efforts to improve the attitude of parents in handling febrile seizures need to be done one of them through health education with the simulation method. The purpose of this research is to know the effect of emergency simulation on parents' attitudes in handling children’s febrile seizures (in Ngampel Village Bancar Tuban). The research method used is a pre-experimental design with a one-group pre-post-test design. The research sample is 28 parents of babies or toddlers in Ngampel Village selected by simple random sampling. Using a cross-sectional approach. The data were analyzed using Wilcoxon’s test. The results showed that most of the respondents before being given an emergency simulation had an attitude in the medium category and after being given an emergency simulation had an attitude in the good category. The result of the statistical test showed that there is an effect of emergency simulation on parents attitudes in handling children’s febrile seizures (in Ngampel Village Bancar Tuban) with a value of p-value 0,000 pada α=0,05 (p<0,05). Expected emergency simulation can improve the attitudes of parents in handling children’s febrile seizures.